Two conceptions of social capital in Malaysia - Abdul Hamid, Ahmad Shukri; Ahmad, Noor Azizah (2015)
This paper discusses two conceptions of social capital in Malaysian society.The discussion is based on the findings of two separate studies on social capital in the state of Kedah, Malaysia. The first study employed a qualitative approach focusing on two religious communities in the Kuala Muda District.The second study utilised a survey method and had produced a localized instrument for measuring social capital. The findings from both studies illuminate some of the types of social capital that can be associated with the Malaysian social fabric.In the first instance social capital can be conceived as emerging from religious communal setting and comprises three (3) different yet interrelated social realms.These types of social capital can further be differentiated based on levels of social organization – the micro-level and macro-level.The second conception of localized social capital suggests that it can be measured based on six (6) areas of communal relations that can typically be found in Malaysian society.It portrays the importance of considering indigenous social setting in formulating localized conception of social capital. This paper concludes with a discussion on the implications that these findings have on social capital research in Malaysia particularly on how they can be utilised to investigate indigenous conceptions of social capital.